Effect of COVID-19 on public distribution system in India - Pathak, Pallavi; Gope, Tapan; Bader, Nadine (International Journal Of Community Medicine And Public Health, 2020)
The COVID-19 pandemic has caused the whole world to face an economic crisis and hence putting people even more at risk of food insecurity; supply chain setup has been disrupted severely due to numerous transport restrictions. There is a need for various components of government machinery to work in complete synergy for aligning services, making provision for supplies and arranging means of delivery to the citizens. This review gives an understanding about the food security situation in India, problem faced by the citizens, in particular the poor and vulnerable population, small and marginal farmers during the COVID-19 pandemic. It also analyses the steps taken by the government of India to address the food security challenges during COVID-19. We have discussed the importance of macrolevel thinking and various measures that can be taken to strengthen public distribution system in India. We have also discussed policies to support the small and marginal farmers, wage laborers, and migrant workers.